2018
DOI: 10.1093/toxsci/kfy216
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Factor FOXO3a Is a Negative Regulator of Cytotoxicity of Fusarium mycotoxin in GES-1 Cells

Abstract: Molecular mechanism and key factors responsible for cytotoxicity against mycotoxin deoxynivalenol (DON) from Fusarium pathogens are rarely elucidated. In this study, rapid increases of ROS were first observed in human gastric epithelial (GES-1) cells under DON exposure. Mitochondrial DNA damage, impaired respiratory chain, and decreased oxygen consumption rate (OCR) values, as well as G2/M cell cycle arrest and apoptosis, were also detected. Via combinatorial approaches of a large-scale microarray of different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 35 publications
3
13
0
Order By: Relevance
“…The inhibition rate reached 80% at all concentrations after 72 hours of DON treatment. Similar experimental phenomena have also been confirmed in the study by Yang et al [56]. In addition, Dai’s [57] research also demonstrated that DON not only causes dose-dependent cytotoxicity, but also causes time-dependent cytotoxicity of mouse endometrial stromal cells.…”
Section: Resultssupporting
confidence: 77%
“…The inhibition rate reached 80% at all concentrations after 72 hours of DON treatment. Similar experimental phenomena have also been confirmed in the study by Yang et al [56]. In addition, Dai’s [57] research also demonstrated that DON not only causes dose-dependent cytotoxicity, but also causes time-dependent cytotoxicity of mouse endometrial stromal cells.…”
Section: Resultssupporting
confidence: 77%
“…NFKB is also reported to modulate HIF-1α expression, the main transcription factor activated by low oxygen concentrations [29]. Another transcription factor, FOXO3a, plays a crucial role in DON toxicity, both through its documented role in the regulation of steroidogenesis as well as its regulation of apoptosis [30]. Accordingly, we evaluated the expression of RelA , FOXO3A, and HIF-1α as well as ERK and JNK.…”
Section: Resultsmentioning
confidence: 99%
“…DON was previously reported to modulate HIF-1α expression in the process of oxidative stress in chickens [36] and constitutively modulates the expression of NFΚB in the inhibition of cancer cell growth [37]. In human gastric epithelial cells, the toxicity of DON was associated with the modulation of apoptosis regulated by FOXO3a [30]. Our results are consistent with these reports and present a significant increase in the expression of RelA , HIF-1α, and FOXO3a after exposure of PCa cells to DON.…”
Section: Discussionmentioning
confidence: 99%
“…The gastrointestinal tract is often an important target for first exposure to these dietary toxins [ 30 , 31 ]. It is reported that FB1 can affect the health of the gastrointestinal tract (GIT) in animals [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%